BOOK REVIEW: Joachim Bahlcke, “Gegenkräfte. Studien zur politischen Kultur und Gesellschaftsstruktur Ostmitteleuropas in der Frühen Neuzeit”, Marburg, Verlag Herder-Institut, 2015, 481 p., ISBN: 978-3-87969-396-2 - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2018)
Marburg, Verlag Herder-Institut, 2015, 481 p., ISBN: 978-3-87969-396-2 Undoubtedly Joachim Bahlcke is one of the most prolific authors in the field of the political, religious, cultural and social East-Central European history of the last three decades. This book confirms it, as it groups several articles addressing what we know as “Gegenkräfte“, i.e. antagonistic or counter forces in East-Central Europe. Due to the fact that the articles were published without any literature update, my review will focus on a single comprehensive question: does the author bring into our knowledge new ways of understanding the East-Central European political, confessional and social history during the Early Modern Era?